PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH PERILAKU JUVENILLE DELINQUENCY DI SMP NEGERI 2 GONDANG TULUNGAGUNG - Asyfailia Khusna; Maskuri Maskuri; Moh Muslim (VICRATINA, 2021)
Juvenile delinquency is a form of social neglect, which results in deviations from a person's behavior. Lately, there have been many cases of delinquency committed by teenage boys and girls. This delinquency causes many negative impacts for themselves, as well as for others. This study aims to prevent juvenile delinquency behavior at SMPN 2 Gondang, by planning, implementing Islamic religious education teachers in learning activities in the classroom or outside the classroom. This study uses a qualitative research method that puts forward the subjective interpretation of the researcher. Researchers used data collection instruments through the process of observation, interviews, and documentation. Using case study research, observation and in-depth interviews with Islamic religious education teachers at SMP Negeri 2 Gondang Tulungagung. The results of this study are; 1) Planning for Islamic religious education teachers is to compile learning rankings with the aim that the implementation of learning is more structured and easier; 2) Implementation of prevention of juvenile delinquency by conducting intracurricular activities, namely teaching and learning activities in the classroom, and extracurricular activities, namely activities of developing skills and interests of students' talents; 3) The results of the PAI teacher's efforts are that juvenile delinquency behavior in SMP Negeri 2 Gondang is reduced in the sense that students do not commit serious delinquency, students follow the rules set by the school, and students win many competitions at the provincial and district levels. Kata Kunci: Juvenille Delinquency, Kenakalan Remaja